2011
DOI: 10.1002/adfm.201101100
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Healing Fibre Reinforced Composites via a Bioinspired Vasculature

Abstract: This paper demonstrates the fi rst steps towards self-healing composites that exploit a design philosophy inspired by the damage tolerance and self-repair functions of bone. Cracking in either fi bre reinforced polymers (FRP) or bone, if left unattended, can grow under subsequent cyclic stresses eventually leading to catastrophic failure of the structure. On detection of cracks, an FRP component must be repaired or completely replaced, whereas bone utilises a series of complex processes to repair such damage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(85 citation statements)
references
References 64 publications
0
85
0
Order By: Relevance
“…Norris et al have further developed this concept with the stimuli triggered delivery of a pre-mixed commercial epoxy SHA into an aerospace grade composite material, when subject to low energy impact damage, to recover compression after impact (CAI) strength. [21][22][23] As previously discussed, [9] the SHAs implemented in this study offer significant improvements over alternative well documented self-healing systems, for example those employing Grubbs' catalyst, [24] polydimethylsiloxane (PDMS)/di-n-butyltin dilaurate (DBTL) [25] and epoxy/maleimide. [26] These improvements include host matrix compatibility, catalytic activity under mild conditions, relatively low cost and toxicity, high stability, commercial availability and system tailorability.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Norris et al have further developed this concept with the stimuli triggered delivery of a pre-mixed commercial epoxy SHA into an aerospace grade composite material, when subject to low energy impact damage, to recover compression after impact (CAI) strength. [21][22][23] As previously discussed, [9] the SHAs implemented in this study offer significant improvements over alternative well documented self-healing systems, for example those employing Grubbs' catalyst, [24] polydimethylsiloxane (PDMS)/di-n-butyltin dilaurate (DBTL) [25] and epoxy/maleimide. [26] These improvements include host matrix compatibility, catalytic activity under mild conditions, relatively low cost and toxicity, high stability, commercial availability and system tailorability.…”
Section: Introductionmentioning
confidence: 94%
“…[21] Initial fracture toughness testing of five baseline FRP specimens at a displacement rate of 2 mm/min resulted in progressive crack propagation along the midplane at an average load of 27.2 N; a failure mode typical of Mode I loaded UD test…”
Section: Benchmark Commercial Healing Systemmentioning
confidence: 99%
“…Active cooling systems are used extensively in electronics, [2] fuel cells, [3,4] high power batteries, [5] micro-electro-mechanical systems (MEMS), [6] and spacecraft systems. [7][8][9] In addition to cooling, vascular networks in PMCs enable self-healing, [10][11][12][13] electromagnetic modulation, [14] and damage detection. [15][16][17] Here, we fabricate a vascular network into each phase of a bilayer nickel-titanium (NiTi)/glass fiber reinforced epoxy hybrid by the Vaporization of Sacrificial Components (VaSC) technique.…”
Section: Introductionmentioning
confidence: 99%
“…Norris et al 8 have shown that parameters such as the vascule diameter [26,27] and orientation 9 relative to the fibre reinforcement [28] strongly affect the ultimate performance of the 10 composite. A key finding is that alignment of the vasculature in the fibre direction is 11 highly preferable as it eliminates the requirement to cut plies and introduce fibre 12 discontinuities into the system.…”
Section: Vascular In-situ Repair / Self-healing 13mentioning
confidence: 99%